A SYSTEMATIC REVIEW OF RISK OF DEVELOPING TYPE 1 DIABETES IN EARLY INFANT FEEDING - M. Hadi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Aim : The primary goal of this study consists of looking at nutritional risk factors, particularly breastfeeding early in infancy, that may be linked to the development of type 1 diabetes and to identify the relationship between these variables and the disease's progression. Methods: Prior as long as July 2015, the Cochrane Library, MEDLINE, EMBASE, Web of Science, and CINAHL were searched for research on any kind of design. In March 2016, MEDLINE and EMBASE were also searched. T1D or T1D-associated autoimmunity (T1DA) development was the major outcome measure. Results: There were nine publications found. Breastfeeding at the moment of gluten administration did not lessen the likelihood of developing T1DA or T1D when compared to gluten administration following weaned. Except for gluten introduction at 3 months or younger vs gluten introduction at later than 3 months, which raised the risk of T1DA in children at high risk of developing T1D, the age of gluten introduction in babies had no influence on the risk of developing T1D. Conclusion: Recent data, primarily from observational studies, disagrees with the idea that early infant feeding habits, such as breastfeeding at gluten administration or infant age at gluten introduction, may reduce the chance of developing T1D. More strong results from randomized controlled trials are required.